2012
DOI: 10.1159/000336029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Environment, Fibrin, and Basic Fibroblast Growth Factor Incorporation on a Canine Autologous Model of Bioengineered Cartilage Tissue

Abstract: We developed a technique to form a bioabsorbable synthetic polymer (polyglycolic acid, PGA) combined with a natural polymer (fibrin) to serve as a scaffold to help retain seeded cells and improve the seeding efficiency of chondrocytes in an implantable construct. This approach was evaluated in a canine autologous implant model of bioengineered cartilage. The implantation site (subcutaneous or intrafascial) and the use of basic fibroblast growth factor (b-FGF) were also evaluated with this system. The intrafasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Isogai et al developed a composite scaffold to fabricate a complicated 3D engineered auricular cartilage with a slow-release b-FGF system. 29,41,42 From *50 to 80 mg/cm 3 b-FGF had been impregnated onto gelatin sponges. The enhanced vascular networks 41 induced by slow-release b-FGF and the proliferated chondrocytes are involved in enhanced chondrogenesis and production of extracellular matrix in cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isogai et al developed a composite scaffold to fabricate a complicated 3D engineered auricular cartilage with a slow-release b-FGF system. 29,41,42 From *50 to 80 mg/cm 3 b-FGF had been impregnated onto gelatin sponges. The enhanced vascular networks 41 induced by slow-release b-FGF and the proliferated chondrocytes are involved in enhanced chondrogenesis and production of extracellular matrix in cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…They had seeded 100 · 10 6 chondrocytes/mL onto the scaffold made of a complex of polyglycolic acid polymer and polypropylene. Isogai and colleagues 41 had reported that impregnation of 160 mg b-FGF per 1 cm 3 scaffold volume with gelatin enhances chondrogenesis and production of extracellular matrix.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have focused on tissue-engineering the condylar cartilage and the disc of the TMJ [Almarza and Athanasiou, 2004;Detamore and Athanasiou, 2005;Dare et al, 2009;Hillel et al, 2009;Morotomi et al, 2012]. This study, for the first time, focused on creating a tissueengineered SM of the TMJ with an original method, because we hold that an SM with abnormal function will cause continuous damage to the cartilage and disc rather than nourish them.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, the fiber diameter of nonwoven polyglycolic acid (mean fiber diameter, 20 μm) is larger than the seeded cell size, and resultant wide spacing between fibers causes seeded cells to leak out without retention in the polyglycolic acid scaffold with concomitant low seeding efficiency. 6 To overcome this problem, we investigated the application of a technique to form polyglycolic acid into nanofibers with diameters and woven patterns similar to those of natural extracellular matrix. The optimal fiber diameter of the scaffold material specific to the tissue to be regenerated is desired; unfortunately, there has been no report elucidating this issue.…”
mentioning
confidence: 99%